Monocytic myeloid-derived suppressor cells reflect tuberculosis severity and are influenced by cyclooxygenase-2 inhibitors. Issue 1 (6th November 2020) - Jøntvedt Jørgensen, Marthe; Jenum, Synne; Tonby, Kristian; Mortensen, Rasmus; Walzl, Gerhard; Du Plessis, Nelita; Dyrhol-Riise, Anne Ma
Abstract: Myeloid-derived suppressor cells (MDSCs) increase in tuberculosis (TB) and may be targets for host-directed therapy (HDT). In this study, we use flow cytometry to analyze the effects of cyclooxygenase-2 inhibitors (COX-2i) on monocytic (M)-MDSCs in blood from TB patients attending a clinical trial of COX-2i. The effects of COX-2i on M-MDSCs and mycobacterial uptake were also studied by an in vitro mycobacterial infection model. We found that M-MDSC frequencies correlated with TB disease severity. Reduced M-MDSC ( P = 0.05) and IDO ( P = 0.03) expression was observed in the COX-2i group. We show that peripheral blood-derived M-MDSCs successfully internalized Mycobacterium bovis and that in vitro mycobacterial infection increased COX-2 ( P = 0.002), PD-L1 ( P = 0.01), and Arginase-1 ( P = 0.002) expression in M-MDSCs. Soluble IL-1β, IL-10, and S100A9 were reduced in COX-2i-treated M-MDSCs cultures ( P < 0.05). We show novel data that COX-2i had limited effect in vivo but reduced M-MDSC cytokine production in vitro. The relevance of COX-2i in a HDT strategy needs to be further explored. Graphical Abstract: Study of Cyclooxygenase-2 inhibitors effects on monocytic Myeloid-derived suppressor cells in host directed therapy clinical trial supported by in-vitro data with reduction of suppressive soluble markers.